Pengaruh Diskusi Refleksi Kasus Terhadap Penerapan Standar Operasional Prosedur Risiko Jatuh di RSUD Pasar Minggu Tahun 2021: The Effect of Case Reflection Discussion on the Implementation of Standard Operating Procedures for Falling Risk at Pasar Minggu Hospital in 2021 - Hafidiah, Hafidiah (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Care-Base Discussion is a highly efficient and effective method to improve and develop the knowledge, experienced, and accountability of a nurse Methods: This study is a quantitative quasi-experiment that used Pre and Post Test Control Group Design method. There were 36 respondents included and they were divided into the control group and the intervention group Results: The majority of respondents in the control group and the intervention group were aged between 24-30 years with a total of 12 respondents (66.67%). Gender, in the majority control group, the respondents were gender, women with a total of 13 people (72.2%) while in the intervention group the majority of respondents were also dominated by women with a total of 16 people (88.99%).  Education both in the control and intervention groups, the majority of respondents had diploma education levels as many as 11 people with a percentage of 61.1%,  pre-test scores in the group control and intervention are in the poor category with a percentage of 100% (18 people), the post-test scores in the control group showed unfavorable results as many as 15 respondents (83.3%) and good results as many as 3 respondents (16.7%). In the intervention group, the post-test scores showed poor results by 1 respondent (5.6%) and good as many as 17 respondents (94.4%), nurses in the application of the Fall Risk Procedure intervention group before DRK was carried out, namely a minimum score of 6 and a maximum of 8 with an average of 7.28, and after DRK the minimum value was 8 and a maximum of 10 with an average of 9.28. Meanwhile, in the control group, the minimum score for the pre-test was 7 and a maximum of 8 with an average of 7.39, while after the post-test the minimum score was 8 and a maximum of 9 with an average of 8.17. Discussion: Based on the results of the research on the effect of Case Reflection Discussion on Compliance with the Application of Standard Operational Procedures for Falling Risk, it can be concluded that DRK can affect the increase in compliance with the application of the Fall Risk SOP at Pasar Minggu Hospital.